Coordinated control strategy for hybrid wind farms with DFIG-based and PMSG-based wind farms during network unbalance. (May 2017) - Yao, Jun; Liu, Ruikuo; Zhou, Te; Hu, Weihao; Chen, Zhe
Abstract: This paper investigates the coordinated control strategy for a hybrid wind farm with doubly fed induction generator (DFIG)-based and direct-driven permanent-magnet synchronous generator (PMSG)-based wind farms during network unbalance. The negative-sequence current output capabilities of DFIG and PMSG systems under unbalanced grid voltage condition are described. Furthermore, by considering both the negative-sequence current capabilities and requirements of different control targets for each control unit, the controllable operating regions of DFIG and PMSG systems are investigated. According to the controllable operating regions, a targets selection scheme for each control unit is proposed to improve the stability of the hybrid wind farms containing both DFIG-based and PMSG-based wind farms during network unbalance, especially to avoid DFIG-based wind farm tripping from connected power grid under severe grid voltage unbalance conditions. Finally, the proposed coordinated control strategy is validated by the simulation results of a 30-MW-DFIG-based wind farm and a 30-MW-PMSG-based wind farm under different operation conditions and experimental results on a laboratory-scale experimental rig under severe grid voltage unbalance conditions. Highlights: The operation principle of hybrid wind farms with DFIG and PMSG is researched. The current output capabilities of the hybrid wind farms are described. The controllable operating regions of DFIG and PMSG systems are deduced. A target selection scheme for the hybrid wind farms is proposed.